Solar‐light‐driven ZnO/biochar treatment of pesticides contaminated wastewater: A practical and computational study - Mahmoud Samy; Mohamed Gar Alalm; Eman Ezeldean; A. El‐Dissouky; Nadia B. E. Badr; Ala'a Al‐Muhtaseb; Nawaf S. Alhajeri; Ahmed I. Osman; Ahmed Tawfik (Energy Science & Engineering, 2022)
Abstract Biochar (BC) was prepared by carbonizing sludge from agricultural lignocellulosic waste fermentation and then used to adsorb lambda‐cyhalothrin (LM), malathion (MA), and oxamyl (OX) as potential pesticides in agrochemical industrial wastewater. Additionally, the photodegradation performance of ZnO and ZnO/Fe was evaluated using various catalyst doses in a constructed parabolic solar collector reactor. The optimal ZnO catalyst dose and reaction time was 1.0 g/L and 135 min. OX, MA, and LM removal increased from 38%, 30%, and 24% in pristine ZnO to 55%, 70%, and 46.9% in the case of the addition of BC with ZnO (ZnO/BC), respectively. The doping of ZnO with iron did not improve the photodegradation efficiency due to the reduction of crystallinity and catalyst affinity towards the pollutants after introducing those ions. The mechanism of degradation was proposed, and the by‐products generated were identified. The total cost was estimated for pure ZnO, the addition of BC with ZnO (ZnO/BC), and the addition of BC with iron‐doped ZnO (ZnO/Fe/BC). The highest binding energy of −44.74 was recorded for BC–OX complex, followed by BC–LM at −42.97. The adsorption of LM, MA, and OX by ZnO/BC is primarily due to the hydrophobic interaction, hydrogen bonding, and π–π interaction. After three cycles of recycling ZnO/BC, the degradation efficiency remained 55–52.5% for OX, 70–65% for MA, and 46.9–42.8% for LM, indicating excellent reusability and stability of the composite catalyst. The low cost of the solar‐light‐driven ZnO/BC process may improve the technique's feasibility for large‐scale implementation.